TOBACCO CONTROL IN INDIA—LOTS NEED TO BE DONE - Singh, C M; Kaushik, Amit; Jain, P K (Indian Journal of Community Health, 2011)
Tobacco use is among the leading causes of preventable premature death and disease all over the world. As per World Health Organization (WHO) estimates, at present, its use kills more than 5 million people each year worldwide and most of these deaths occur in low and middle-income countries. If immediate steps are not taken to tackle the problem gap in deaths between low and middle-income countries and high-income countries is expected to widen further over the next several decades. It is estimated that if current trends of tobacco use persist, it will take a toll of more than 8 million lives worldwide every year by 2030, out of these 80% premature deaths are expected to occur in low and middle-income countries. By the end of this century, tobacco may kill a billion people or more unless urgent action is taken.1 Deaths attributed to tobacco use are increasing in India and account for about one sixth of the world’s tobacco-related deaths. Estimations on tobacco-related deaths revealed the fact that smoking was expected to kill nearly one million Indians by the early 2010.2